Successful Keys to Enhancing Aerostreet Purchase Decisions in Semarang City through Co-Branding, Content Marketing, and Reviews - Mochammad Sulthan Ariq Ramadhan; Febrianur Ibnu Fitroh Sukono Putra; Bara Zaretta; Haunan Damar (Jurnal Ekonomi dan Bisnis, 2026)
Research aims to explore the influence of Co-Branding, Content Marketing, and online customer reviews on the decision to purchase Aerostreet shoe products in Semarang. This Study uses quantitative analysis techniques with a sample of 120 consumers of Aerostreet shoe products in Semarang. The participants in this Study were residents of Semarang who had purchased Aerostreet shoe products. The sampling technique used was a purposive sampling method. Statistical tests, classical assumption tests, and multiple linear regression tests were used to evaluate the data. The findings of this Study indicate that Co-Branding and Content Marketing have a positive and significant influence on purchasing decisions. In contrast, Online Customer Reviews have a positive but insignificant influence.   Penelitian ini bertujuan untuk mengeksplorasi pengaruh Co-Branding, Content Marketing, dan Online Customer Review tersebut terhadap keputusan pembelian produk Sepatu Aerostreet di kota Semarang. Penelitian ini menggunakan teknik analisis kuantitatif dengan sampel diperoleh sebanyak 120 konsumen produk sepatu Aerostreet di kota Semarang. Partisipan penelitian ini adalah warga Semarang yang pernah melakukan pembelian produk sepatu Aerostreet. Teknik pengambilan sampel yang digunakan adalah metode purposive sampling. Uji statistik, uji asumsi klasik dan uji regresi linear berganda digunakan untuk mengevaluasi data. Temuan dari penelitian ini menunjukkan bahwa Co-Branding dan Content Marketing memiliki pengaruh yang positif dan signifikan terhadap keputusan pembelian, sedangkan Online Customer Review memiliki pengaruh yang positif namun tidak signifikan.